Individual, family, and environmental correlates of fundamental motor skills among school-aged children: a cross-sectional study in China - Yuxiu He; Lin Zhou; Wei Liang; Qi Liu; Wanxin Liu; Shijian Wang (BMC, 2024)
Abstract Objective This cross-sectional study examined the socio-ecological factors influencing fundamental motor skills (FMS) in Chinese school-aged children. Methods A total of 1012 parent-child pairs were randomly sampled between March-1st and April-15th, 2022. Based on the socio-ecological model of Children's FMS, three levels of factors: individual-level (e.g., demographic, physical, psychological, and behavioral characteristics of children), family-level (e.g., caregiver demographics, parental support, and socioeconomic status), and environmental factors (e.g., availability of physical activity equipment) were assessed using self-reported scales (e.g., the Self-perception Profile for Children, the Physical Activity Enjoyment Scale, and the 12-item Psychological Well-Being Scale for Children) and objective measures (e.g., ActiGraph GT3X, the Chinese National Student Physical Fitness Standard, and the Test of Gross Motor Development-Third Edition). Multi-level regression models were employed using SPSS. Results The results demonstrated that children's age, sex, physical fitness, parental support, and the quality of home and community physical activity environments consistently influenced all three types of FMS, including locomotor, ball, and composite skills. Additionally, seven individual-level factors (children's age, sex, body mass index, light physical activity, sleep duration, perceived motor competence, and physical fitness) were associated with different types of FMS. Conclusions The findings underscore the multidimensional and complex nature of FMS development, with individual-level factors playing a particularly significant role. Future research should adopt rigorous longitudinal designs, comprehensive assessment tools covering various FMS skills, and objective measurement of parents' movement behaviors to better understand the strength and direction of the relationship between socio-ecological factors and children's FMS.